Bebe, vamos a comer! = Baby, let's eat! - Lomp, Stephan (New York : Workman Publishing Co., Inc., 2018)
Explora un arco iris de alimentos deliciosos en un libro que es indestructible.
Explore the rainbow of delicious food from an indestructible book.
"Bilingual: Spanish and English"--Cover.
Resiste mordidas. No se rompe. No es toxico. 100% lavable.
Para edades de 0 y más!
Text in Spanish and English.
Keywords: Spanish language materials -- Bilingual -- Juvenile literature; Materiales bilingues en espanol -- Literatura juvenil; Infants -- Juvenile literature; Food -- Juvenile literature; Ninos lactantes -- Literatura juvenil; Alimentos -- Literatura juvenil